The Influence of Organizational Culture on Employee Performance Mediated by Leadership in The Cooperative, SMEs, Industry, and Trade Office of Bungo Regency - Novriansyah, Yudhi; Royati, Erlina; Yeni, Misra (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The Office of Cooperatives, SMEs, Industry, and Trade of Bungo Regency strives to improve employee performance with influencing factors work culture, mediated by leadership. In this study, there are 33 samples using purposive sampling technique. Meanwhile, the data analysis technique uses the SmartPLS 4.0 program. The results of this study show that Organizational Culture significantly influences Leadership, Work Culture significantly influences Employee Performance, and Leadership significantly influences Employee Performance. Indirectly, Leadership is able to mediate the influence of Work Culture on Employee Performance in the Cooperatives, SMEs, Industry, and Trade Office of Bungo Regency.